PENGARUH KEPERCAYAAN, TRANSPARANSI DAN KUALITAS PELAYANAN TERHADAP LOYALITAS MUZAKKI LAZ SOLO PEDULI - Sri Muljaningsih; Muhammad Syfaul Adib (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This article aims to analyze the effect of trust, transparency, and service quality on the loyalty of the muzakki of the amil zakat institution Solo Peduli. This research is a quantitative study using a questionnaire using a liker scale and the method is calibrated using multiple linear regression analysis with the help of the SPSS application. There were 40 sample respondents consisting of 10 male respondents and 30 female respondents. The results of the study show that the trust factor and service quality have a significant influence on the loyalty of Solo Peduli muzakki, while the transparency factor has no significant effect on the loyalty of Solo Peduli muzakki. As for the trust in transparency, and the quality of service explained by 61.2% of the loyalty of muzakki Solo Peduli